Pemikiran pendidikan Yusuf Al-Qardhawi dalam Kitab Al-‘Aql Wa al-‘Ilm Fi Al-Qur'an - Fitrah, Meri; Hamka, Syamsuar (Tawazun: Jurnal Pendidikan Islam, 2022)
Intellect is a device that was given by Allah SWT to humans specifically. Human has the ability to involve civilization and advance their life with their intellect. This research aims to find out the educational thinking according to Yusuf al-Qardhawi in his book "al-'Aql Wa al-'Ilm Fi al-Qur'an”. This study is qualitative research with a literature study approach. The findings of the educational thought of Yusuf al-Qardhawi have been obtained: The purpose of education is the formation of intelligent minds. Educational methods according to Yusuf al-Qardhawi in this book are Tafakur and Tadzakur. In addition, it is obtained by a student that there are three processes of gaining knowledge, those are direct learning, asking questions, and "journey” (rihlah). Abstrak Akal adalah perangkat yang diberikan oleh Allah SWT kepada manusia secara khusus. Dengan akal manusia mampu membangun peradaban dan memajukan kehidupannya. Penelitian ini bertujuan untuk mengetahui pemikiran pendidikan menurut Yusuf Al-Qardhawi dalam kitab al-‘Aql Wa al-‘Ilm Fi Alquran. Penelitian ini adalah penelitian kualitatif dengan pendekatan studi pustaka. Temuan pemikiran pendidikan Yusuf Al-Qardhawi diperoleh: Tujuan pendidikan adalah terbentuknya akal yang cerdas. Adapun metode pendidikan menurut Yusuf Al-Qardhawi dalam kitabnya adalah Tafakkur dan Tadzakkur. Selain itu diperoleh bagi seorang murid proses mendapatkan ilmu ada tiga, yaitu belajar langsung, bertanya dan "rihlah”.